2020
DOI: 10.1097/sap.0000000000002330
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Intention Healing After Mohs Surgical Excision as an Alternative to Surgical Repair

Abstract: Background A multitude of reconstructive options exist for patients after Mohs surgery of cutaneous neoplasms of the head and neck. Secondary intention healing is often overlooked and underused but has numerous advantages, including superior esthetic outcomes compared with surgical reconstruction for wounds that exhibit particular characteristics. The ability to predict cosmetic results based on wound characteristics can greatly help in the decision between surgical repair and secondary intention h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Furthermore, it was also reassuring that no adverse events (AEs) were recorded in patients whose wounds were allowed to heal by SIH (Supplementary Table S2), supporting several studies that have shown that SIH can provide excellent cosmetic results. 10,11 Although SIH is not suitable for every wound defect, generally being reserved for concave anatomical locations, 12 these results should encourage general dermatologists performing skin surgery that SIH should not be overlooked for wound reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also reassuring that no adverse events (AEs) were recorded in patients whose wounds were allowed to heal by SIH (Supplementary Table S2), supporting several studies that have shown that SIH can provide excellent cosmetic results. 10,11 Although SIH is not suitable for every wound defect, generally being reserved for concave anatomical locations, 12 these results should encourage general dermatologists performing skin surgery that SIH should not be overlooked for wound reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 For the nose, the best esthetic outcomes were seen in wounds located on the nasal ala, a concave surface, and poorer results were seen on the nasal tip, a convex surface. 7 Statistical evidence has also shown that concave areas of the face are prone to heal excellently, especially if these wounds are small, superficial, and located near the medial canthus and medial cheek. 6 Furthermore, on concave surfaces secondary intention healing produces cosmetic results that are superior to those produced by flaps or grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation criteria referred to previous literatures. 6,7 Excellent was defined as a scar with no mismatch in edge contour and a good color match or only minor hypopigmentation to surrounding skin. Good was defined as little mismatch in edge contour and good color match or only minor hypopigmentation to surrounding skin.…”
Section: Methodsmentioning
confidence: 99%
“…Areas that are prominent and convex (i.e., the nasal tip) should be repaired via other methods. 18,19 Other cited benefits include avoidance of further invasive procedures, lack of donor site morbidity, and this being a viable option for those who are not optimal surgical candidates for other reconstructive options. 18 This option may require diligent wound care and patience from the patient.…”
Section: Abrasions and Appropriate Cases For Secondary Intention Healingmentioning
confidence: 99%
“…18,19 Other cited benefits include avoidance of further invasive procedures, lack of donor site morbidity, and this being a viable option for those who are not optimal surgical candidates for other reconstructive options. 18 This option may require diligent wound care and patience from the patient. There is also the possibility of hypopigmentation of the area, which may be more cosmetically unacceptable in higher Fitzgerald skin types.…”
Section: Abrasions and Appropriate Cases For Secondary Intention Healingmentioning
confidence: 99%